Migration of rice planthoppers and their vectored re-emerging and novel rice viruses in East Asia - Otuka, Akira (Frontiers in Microbiology, 2013)
This review examines recent studies of the migration of three rice planthoppers, Laodelphax striatellus, Sogatella furcifera, and Nilaparvata lugens, in East Asia. Laodelphax striatellus has recently broken out in Jiangsu province, eastern China. The population density in the province started to increase in the early 2000s and peaked in 2004. In 2005, Rice stripe virus (RSV) viruliferous rate of L. striatellus peaked at 31.3%. Since then, rice stripe disease spread severely across the whole province. Due to the migration of the RSV vectors, the rice stripe disease spread to neighboring countries Japan and Korea. An overseas migration of L. striatellus that occurred in 2008 was analyzed, when a slow-moving cold vortex, a type of low pressure system, reached western Japan from Jiangsu, carrying the insects into Japan. Subsequently the rice stripe diseases struck these areas in Japan severely. In Korea, similar situations occurred in 2009, 2011, and 2012. Their migration sources were also estimated to be in Jiangsu by backward trajectory analysis. Rice black-streaked dwarf virus, whose vector is L. striatellus, has recently re-emerged in eastern China, and the evidence for overseas migrations of the virus, just like the RSV’s migrations, has been given. A method of predicting the overseas migration of L. striatellus has been developed by Japanese, Chinese, and Korean institutes. An evaluation of the prediction showed that this method properly predicted migration events that occurred in East Asia from 2008 to 2011. Southern rice black-streaked dwarf virus (SRBSDV) was first found in Guangdong province. Its vector is S. furcifera. An outbreak of SRBSDV occurred in southern China in 2009 and spread to Vietnam the same year. This disease and virus were also found in Japan in 2010. The epidemic triggered many migration studies to investigate concrete spring-summer migration routes in China, and the addition of migration sources for early arrivals in Guangdong and Guangxi have been proposed. Nilaparvata lugens is also an important insect pest of rice. Its migration situations on the Indochina peninsula and return migrations in China are discussed.